Study of Rural Industries Projects - Planning Commission (Planning Commission, 1966)
The primary objective is to bring about a cooperative agro-industrial economy. This involves all round development of agriculture, irrigation, communication, social services, etc. For this purpose, the initiative and effort of local communities will have to be stimulated and mobilised to the fullest extent. Among the most important measures to be taken towards the diversification of the rural economy is the building up of industries based on agriculture and other resources and the vigorous development of non—agricultural along with agricultural occupations. The most difficult problem in the rural areas is to create, maintain and expand non-agricultural employment. Even the success of efforts in other directions will depend on progress achieved in building up industries suited to local areas.
Design Schedules Etc. and Instructions